Our undemocratic constitution : where the constitution goes wrong (and how we the people can correct it) - Levinson, Sanford, 1941- (Oxford University Press, 2006)
Prelude: The Wisdom of Thomas Jefferson. Introduction: A Tale of Two Signings. 1. The Ratification Referendum: Sending the Constitution to a New Convention for Repair. 2. Our Undemocratic Legislative Process. 3. The Legacy of Article II: Too-Powerful Presidents, Chosen in an Indefensible Process, Who Cannot Be Displaced Even When They Are Manifestly Incompetent. 4. Life Tenure for Supreme Court Justices: An Idea Whose Time Has Passed. 5. The Constitution as Creator of Second-Class Citizens. 6. The Impermeable Article V. 7. Disenchantment and Desire: What Is to Be Done?. Coda: The Wisdom of Woo.